An unusual presentation of human immunodeficiency virus and dengue coinfection - Dutta, Meghna; Chatterjee, Suddhasatwya (Eastern Journal of Medical Sciences, 2020)
The global incidence of dengue has grown dramatically in recent decades, with around half of the world’s population currently at risk. Despite an overlapping epidemiology, limited data are available on human immunodeficiency virus (HIV) and dengue coinfection. Some reported evidence suggests that the patients with HIV infection are more at risk of a severe dengue outcome, while other reports suggest a transitory inhibition of the HIV-1 viral load, as well as a benign clinical progression of dengue. Our case is of a 44-year-old HIV-infected obese gentleman with typical features of dengue infection. He was closely monitored and his clinical profile was thoroughly studied during in-hospital stay and post-discharge. However, further research is required to comprehend the pathology, as well as the clinical course of these coinfections.